Influencia de la enseñanza del idioma extranjero en el proceso de enseñanza aprendizaje de los niños y niñas del primer año de educación básica de la escuela fiscal mixta Dr. Eulogio Serrano Armijos de la ciudad de Machala provincia de El Oro, periodo lectivo: 2011-2012. - García, Consuelo Elizabeth (2015)
The objective of this research, is to promote quality learning and educational warmth and influence teaching a second language to children, to strengthen their potential for full and harmonious development through learning of linguistic codes based on English. Teaching English to children of five and six years old is very important, because through motivation, we will awaken in them, emotions, creativity, participation and dynamism through, chanting songs in the language foreign and a variety activities, enabling them to develop new skills in their personal formation. According to the results of the investigation, it has made to demonstrate the lack of methods and techniques of teaching by the teachers and the lack of use of didactics resources, have blocked the interest and active participation of children, for this reason my proposal is based on the design of a English songs guide and activities as support material for teachers in the implementation of daily classroom activities and also contribute to emotional and integral development of children in the first year of basic education.